Comparison of rectal indomethacin, diclofenac, and naproxen for the prevention of post endoscopic retrograde cholangiopancreatography pancreatitis. Issue 3 (March 2017) - Mohammad Alizadeh, Amir H.; Abbasinazari, Mohammad; Hatami, Behzad; Abdi, Saeed; Ahmadpour, Forozan; Dabir, Shideh; Nematollahi, Aida; Fatehi, Samira; Pourhoseingholi, Mohammad A.
Abstract : Background and aim: NSAIDs are commonly utilized for the prevention of post endoscopic retrograde cholangiopancreatography pancreatitis (PEP). However, not much is known about the most effective drug in preventing this complication. This study aims to clarify which drug (indomethacin, diclofenac, or naproxen) is most effective for the prevention of post endoscopic retrograde cholangiopancreatography (ERCP). Materials and methods: In a double-blind, randomized study, patients received a single rectal dose of one of the three drugs 30 min before undergoing ERCP: diclofenac (100 mg), indomethacin (100 mg), or naproxen (500 mg). The primary outcome measured was the development of pancreatitis. The levels of serum amylase, lipase, lipoxin A4, and resolvin E1 were measured before ERCP, and at 24 h after the procedure. Results: Three hundred and seventy-two patients completed the study. The overall incidence of PEP was 8.6%, which occurred in five of the 124 (4%) patients who received diclofenac, seven of the 122 (5.8%) patients who received indomethacin, and 20 of the 126 (15.9%) patients who received naproxen. There were no significant differences in amylase and lipase levels among the three groups ( P =0.183 and 0.597, respectively). Unlike patients in the naproxen group, patients in the diclofenac and indomethacin groups showed a significant increase in lipoxin A4 and resolvin E1 ( P =0.001 and 0.02, respectively). Conclusion: Diclofenac and indomethacin patient groups had a lower incidence of PEP than the naproxen group.